2021
DOI: 10.1177/20458940211025240
|View full text |Cite
|
Sign up to set email alerts
|

Vascular cell‐specific roles of mineralocorticoid receptors in pulmonary hypertension

Abstract: Abnormalities that characterize pulmonary arterial hypertension (PAH) include impairment in the structure and function of pulmonary vascular endothelial (EC) and smooth muscle cells (SMC). Aldosterone levels are elevated in human PAH and in experimental pulmonary hypertension (PH), while inhibition of the aldosterone-binding mineralocorticoid receptor (MR) attenuates PH in multiple animal models. We explored the role of MR in ECs and SMCs in using cell specific MR knockout mice exposed to sugen/hypoxia-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 66 publications
(163 reference statements)
2
14
0
Order By: Relevance
“…The molecular mechanism underlying the protective effects of finerenone against the pulmonary vascular remodeling in the monocrotaline and SuHx rats remains unknown; however, our findings indicate that it may partly be mediated by a decrease in PA-SMC proliferation and a reduction of inflammatory cell infiltration in lungs of finerenone-treated monocrotaline and SuHx rats. These data are consistent with the recent study from Menon and colleagues, 21 which showed that the degree of perivascular lung inflammation is higher in mice with a smooth muscle-specific deletion of MR when they are subjected to SU5416 in combination with chronic hypoxia. Consistent with these results, we also found a significant increase in the percentage of KI67-positive pulmonary vascular cells and a perivascular accumulation of CD68-positive cells in lungs of hMR + mice.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The molecular mechanism underlying the protective effects of finerenone against the pulmonary vascular remodeling in the monocrotaline and SuHx rats remains unknown; however, our findings indicate that it may partly be mediated by a decrease in PA-SMC proliferation and a reduction of inflammatory cell infiltration in lungs of finerenone-treated monocrotaline and SuHx rats. These data are consistent with the recent study from Menon and colleagues, 21 which showed that the degree of perivascular lung inflammation is higher in mice with a smooth muscle-specific deletion of MR when they are subjected to SU5416 in combination with chronic hypoxia. Consistent with these results, we also found a significant increase in the percentage of KI67-positive pulmonary vascular cells and a perivascular accumulation of CD68-positive cells in lungs of hMR + mice.…”
Section: Discussionsupporting
confidence: 93%
“…However, Menon et al 21 recently reported that endothelial MR deletion was not sufficient to protect mice exposed to chronic hypoxia combined with SU5416 injection. However, these 2 different studies found beneficial effects of MR inhibition by eplerenone 12 and spironolactone 21 in these mouse models of experimental PH, respectively. Taken altogether, these studies reveal cell-type specific roles of MR in the context of PAH that are consistent with the decrease in PA-SMC proliferation and the reduction of inflammatory cell infiltration observed in lungs of finerenone-treated monocrotaline and SuHx rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicate that the beneficial effects of MRAs on PH may be mainly mediated through the blockade of MR in ECs with indirect effects on PASMCs. It is important to note that this finding could not be reproduced in another study using the hypoxia-sugen model (47). EC-specific MR deletion has been shown to exert benefits on the RV in the hypoxia-sugen mouse model by regulating RV E-selectin and collagen III expression and attenuating RV perivascular fibrosis but did not improve PH (47).…”
Section: Genetic Manipulation Of Mr In Ph Animal Modelsmentioning
confidence: 93%